Mechanics of the confined functionally graded porous arch reinforced by graphene platelets. (15th December 2019) - Li, Zhaochao; Zheng, Junxing; Zhang, Zhen
Highlights: The buckling load of the confined FGP-GPLs arch under thermal rise field is obtained theoretically. The analytical buckling load is validated successfully by the numerical simulation. The thermal rise field has a considerable influence on the buckling load of the confined FGP-GPLs arch. The confinement effect is quantized by defining a ratio of the buckling load between the confined and unconfined arches. Abstract: This paper presents the stability mechanism of the confined functionally graded porous (FGP) arch reinforced by graphene platelets (GPLs). The Halpin-Tsai micromechanics theory is used to evaluate the distribution of Young's modulus in the cross-section of the arch. The Gaussian random field is employed to describe the porosity coefficient and mass density. Both pores and GPLs are distributed symmetrically to the mid-surface of the arch. Theoretical predictions are obtained to express the buckling load (load bearing capacity) based on the nonlinear thin-walled shell theory. Excellent numerical verification is obtained by comparing the buckling load, as well as the equilibrium paths with the theoretical predictions. Moreover, a confinement factor is defined to quantize the confinement effect between the confined and unconfined arches. Finally, the buckling load may be influenced by the following parameters: thermal rise field, porosity coefficient, central angle of the arch, weight fraction and geometric parameters of GPLs, friction coefficient, deformability of the medium. These parameters are analyzed and discussed.